Revitalização do centro histórico de São Paulo e habitação popular: microeconomia e microgerografia - Cotelo, Fernando Cardoso (2009)
This doctoral dissertation is a research on the production of low-income housing in a context of a revitalizing programme for the central districts of São Paulo. The argument revisits the mainstream urban microeconomic approach and confronts it with an alternative theoretical approach. To this purpose, in order to access the extension and geographical pattern of degradation, a field study was conducted through actual observation of underoccupied real estate traits and their identification in satellite images as well as data treatment using geographical information systems. The data corroborate the plausibility of the alternative approach and indicate some of the local socioeconomic characteristics that contribute to the present state of degradation. The data analysis then suggests factors that may have lead to the poor performance of the low-income housing production programme in the larger downtown revitalization agenda.